Post Mortem Organ Weight at Bhayangkara Pekanbaru Polda Riau Hospital, Indonesia (Indian Journal of Forensic Medicine & Toxicology, 2020)
Post mortem organ weight is one of indicator that serves as supporting evidence in determining the causeof death, because if there is a difference between the post mortem organ weight with normal organ weightindicates the occurrence of pathological conditions that may be related to the cause of death. The objectiveof this study was to determine post mortem organ weight in autopsy cases at Bhayangkara Pekanbaru PoldaRiau Hospital in 2017-2018. This research is a retrospective descriptive study using secondary data. Datawere obtained from autopsy data in the forensic section of Bhayangkara Pekanbaru Polda Riau Hospital in2017-2018. Data were analyzed by using univariate analysis carried out on each variable of the researchresults. The results of this study were obtained from twenty one autopsy cases with a mean value of organweight: the brain (1334.29 grams), liver (1130.90 grams), right lung (370.48 grams), left lung (311.24 grams)gram), heart (275.33 grams), left kidney (114.52 grams), right kidney (114.00 grams), and spleen (113.43grams). Organs in men are heavier than women, except the liver. Organ weight has decreased in old age.People with short bodies tend to have lighter organ weights than people with tall bodies. The conclusion ofthis study is the average value of post mortem organ weight in this study is different from the weight valueof organs found in forensic textbooks.